1997
DOI: 10.1007/bf03168704
|View full text |Cite
|
Sign up to set email alerts
|

A general technique for automatic left ventricle boundary validation: Relation between gray scale cardioangiograms and observed boundary errors

Abstract: This article presents an automatic left ventricle boundary validation technique using the gray scale cardioangiograms, the observed boundary errors, and the left ventricle boundaries from any source that needs to be validated. This validation technique is based on the gray scale information near the boundary of the left ventricle in the cardioangiograms. Using a mutually exclusive window of fixed size, which is centered on the left ventricle boundary vertex and along the left ventricle contour, we compute a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Suri et al [247] developed a general and automatic validation technique that could detect the LV boundaries whose mean end frame boundary errors were above a forced before calibration. * shows the best performance.…”
Section: General Purpose LV Validation Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…Suri et al [247] developed a general and automatic validation technique that could detect the LV boundaries whose mean end frame boundary errors were above a forced before calibration. * shows the best performance.…”
Section: General Purpose LV Validation Techniquementioning
confidence: 99%
“…Singh et al [210], Wikins et al [209] and McInerney et al [228] showed the implementation of fitting snakes to cardiac data but lacked a validation scheme. Suri et al [247] presented a validation scheme to find whether the estimated curve was at its correct position. (d) Robustness can only be confirmed once the algorithm is able to handle a large volume of data sets with normal and abnormal studies.…”
Section: Cardiac Softwarementioning
confidence: 99%
See 2 more Smart Citations